Islet-Resident Dendritic Cells and Macrophages in Type 1 Diabetes: In Search of Bigfoot’s Print - Zirpel, Henner; Roep, Bart O. (Frontiers in Endocrinology, 2021)
The classical view of type 1 diabetes assumes that the autoimmune mediated targeting of insulin producing ß-cells is caused by an error of the immune system. Malfunction and stress of beta cells added the target tissue at the center of action. The innate immune system, and in particular islet-resident cells of the myeloid lineage, could function as a link between stressed ß-cells and activation and recognition by the adaptive immune system. We survey the role of islet-resident macrophages and dendritic cells in healthy islet homeostasis and pathophysiology of T1D. Knowledge of islet-resident antigen presenting cells in rodents is substantial, but quite scarce in humans, in particular regarding dendritic cells. Differences in blood between healthy and diseased individuals were reported, but it remains elusive to what extend these contribute to T1D onset. Increasing our understanding of the interaction between ß-cells and innate immune cells may provide new insights into disease initiation and development that could ultimately point to future treatment options. Here we review current knowledge of islet-resident macrophages and dendritic cells, place these in context of current clinical trials, and guide future research.